FABRIKASI BATERAI ZN-UDARA DENGAN VARIASI LARUTAN PH NETRAL SEBAGAI ELEKTROLIT - Gustine Adios, Celfi
One of the primary candidates for energy storage technology is Zn-air battery because it has a high theoretical energy density in theory. The Zn-air battery consists of the abundant Zn anode and bifunctional electrocatalyst on the cathode which can be derived from the biomass. However, one of the main problems of Znair battery is the electrolyte. The high corrosiveness of alkaline-based electrolyte can reduce the battery life and hinder the commercialization of Zn-air batteries. In addition, the rapid carbonization of the electrolyte can promote the formation of Zn dendrites during the charge and discharge. In this case, a neutral or nearly neutral solution can be used to replace the alkaline-based electrolyte for Zn-air battery. Alternative biomass electrocatalyst, such as cranberry bean shell (Phaseolus vulgaris L.) derived carbon is introduced. The performance of the Zn-air batteries with cranberry bean shell derived carbon were measured using seawater, Phosphate Buffered Saline solution (PBS), and 0,1M alkaline KOH. The cranberry bean shell derived carbon electrocatalyst in 0,1M PBS solution and seawater show a good onset potential, which is about 0,99 V and 0,81 V, respectively. When the electrocatalyst is used in a Zn-air battery with PBS 0,1M electrolyte, it produces a high peak power density of 6,47 mW cm-2 and stable cycling performance for up to 100 hours with 300 charge-discharge cycles. This results demonstrates the use of neutral electrolytes for Zn-air battery application, with environmental and sustainable added value.